Implementasi Program Bina Prestasi dalam Mengembangkan Minat dan Bakat Siswa di MTsN 6 Ponorogo - Khasanah, Pita; Hakim, Lukman; Nazira, Putri; Laela, Putri Nur (Southeast Asian Journal of Islamic Education Management, 2024)
The development of students' interests and talents is one of the important things to implement. So that the abilities possessed by students can develop optimally. The focus of this research is to find out the implementation of the achievement development program in the fields of Language, tahfidz, and IT at MTsN 6 Ponorogo. This research uses a qualitative approach. This research employs a descriptive case study approach. Data collection uses interview, observation, and documentation techniques. The data analysis model used includes data collection, data condensation, data presentation, and conclusions drawn. The results of this study show: 1) the implementation of the achievement development program in the field of language, 2) the implementation of the achievement development program in the field of tahfidz, 3) the implementation of the achievement development program in the IT field, 4) the obstacles faced in the implementation of the achievement development program, namely the lack of enthusiasm for learning of students. The implementation of diverse learning processes within the achievement development program helps to refine students' skills and nurture their talents and interests. The selection of learning strategies and the selection of the right curriculum in the student learning process will greatly affect the development of their interests and talents. This is evidenced by the many alumni of the MTsN 6 Ponorogo achievement development program who have achievements.